Effect of Managerial Style and Implementation of Computer-Based Accounting Information System (CBAIS) on Managerial Performance of Indonesian Sugar Industries: A Descriptive Study - Asep Darmansyah; Tettet Fitrijanti (Current Aspects in Business, Economics and Finance Vol. 2, 2022)
The goal of this research was to discover a solution to an issue involving the impact of managerial style and the installation of a computer-based accounting information system (CBAIS) on the managerial performance of Indonesian sugar industries. This research was conducted through deductive analysis supported the phenomenon then sought evidence through survey to several sugar industries in Indonesia to get the empirical data. This is a descriptive (explanatory) study that uses hypothesis testing to describe the causal link between particular variables. The managerial style of using management accounting information on sugar industries in Indonesia is classified as interactive, which means that managers utilize management accounting information to include employees and subordinates in decision-making activities on a regular and personal basis. The application of CBAIS to Indonesian sugar industry is categorized as moderate, indicating that the situation is neither poor nor excellent. Managerial style and CBAIS adoption have a substantial impact on the success of Indonesian sugar businesses.